Early-life medical care and human capital accumulation - N. Meltem Daysal; Jonas Cuzulan Hirani (IZA World of Labor, 2021)
Ample empirical evidence links adverse conditions during early childhood (the period from conception to age five) to worse health outcomes and lower academic achievement in adulthood. Can early-life medical care and public health interventions ameliorate these effects? Recent research suggests that both types of interventions may benefit not only child health but also long-term educational outcomes. In some cases, the effects of interventions may spillover to other family members. These findings can be used to design policies that improve long-term outcomes and reduce economic inequality.
Keywords: I11; I12; I18; I21; J13; 330; medical care; public health; children; schooling; test scores; human capital